Risk of violent crime may be associated with hippocampal‐dependent cognitive function in older African Americans. (20th December 2022) - Tan, Genesis; Gimenez‐Santana, Alejandro; Fausto, Bernadette A.; Esiaka, Darlingtina; Gluck, Mark A.
Abstract: Background: Research on Area Deprivation Index (ADI) suggests that the social environment and neighborhood stressors (e.g., violent crime risk) play a role in later‐life cognitive function. However, most of the research linking ADI and cognitive function has been conducted on non‐Hispanic white American samples. Further, while the ADI is useful in facilitating efficient integration of social determinants of health (SDOH) into models of cognitive aging, it does not take into account micro‐level measures of neighborhood stressors which may also affect cognitive function. Therefore, the purpose of the current study is to determine whether violent crime risk contributes to later‐life cognitive function above and beyond ADI in older African Americans. Methods: Participants are part of an ongoing study at Rutgers University‐Newark called the Pathways to Healthy Aging in African Americans, a university‐community collaboration fostered over 16 years (2006‐2022) of community engagement, health education, and public service. Analyses included 149 older African Americans aged 60 and above ( M age = 68.68, SD = 7.25; M edu = 13.99, SD = 2.43; n = 149). Cognitive function was assessed via the acquired equivalence task, a measure of one's ability to generalize past learning to novel task demands. Violent crime risk was calculated using the Risk Terrain Modeling technique, a geospatial risk assessment that evaluates the influence of the built environment on the distribution of crime. Results: A multiple linear regression was run to examine the relationship between violent crime risk and cognitive function. Violent crime risk was significantly associated with acquired equivalence task performance, F (6, 142) = 5.948, p = .024, adj. R 2 = .167, even after controlling for ADI, age, education, and depression. The results showed that individuals living in areas with higher risk of violent crime had poorer ability to generalize past learning to novel task demands. Conclusion: Our findings suggest that for African Americans in an urban setting, hyper‐local violent crime risk appears to be supplemental with ADI at capturing the impact of neighborhood disadvantage on cognitive function and Alzheimer's disease risk. Thus, for African American individuals' later‐life cognitive health, it is important to consider micro‐level measures of neighborhood stressors such as violent crime risk.